2021
DOI: 10.1038/s41598-021-99441-3
|View full text |Cite
|
Sign up to set email alerts
|

Potential impacts of polymetallic nodule removal on deep-sea meiofauna

Abstract: Deep seabed mining is potentially imminent in the Clarion Clipperton Fracture Zone (CCFZ; northeast Pacific). Seabed collectors will remove polymetallic nodules and the surrounding surface sediments, both inhabited by meiofauna, along their path. To determine potential impacts of polymetallic nodule removal, we investigated the importance of nodule presence for the abundance, composition and diversity of sediment meiofauna, and evaluated the existence and composition of nodule crevice meiofauna in the Global S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Both nodules and sediments from sites within APEI‐6 displayed significant chemical differences from those in UK‐1, including higher levels of iron and cobalt (Menendez et al, 2019). The presence of nodules plays a key role in structuring metazoan communities and diversity within the CCZ, proving hard substrate for the growth of sessile mega‐ and macrofauna such as cnidarians, polychaetes, and sponges, as well as habitat for meiofauna such as nematodes, tardigrades, and harpacticoid copepods (De Smet et al, 2017; Miljutina et al, 2010; Pape et al, 2021; Simon‐Lledó et al, 2019). It has been suggested that sediment shear strength can influence macrofaunal diversity patterns (Chuar et al, 2020); however, it is currently unknown if subtle changes in nodule geochemistry influence biodiversity and community composition.…”
Section: Discussionmentioning
confidence: 99%
“…Both nodules and sediments from sites within APEI‐6 displayed significant chemical differences from those in UK‐1, including higher levels of iron and cobalt (Menendez et al, 2019). The presence of nodules plays a key role in structuring metazoan communities and diversity within the CCZ, proving hard substrate for the growth of sessile mega‐ and macrofauna such as cnidarians, polychaetes, and sponges, as well as habitat for meiofauna such as nematodes, tardigrades, and harpacticoid copepods (De Smet et al, 2017; Miljutina et al, 2010; Pape et al, 2021; Simon‐Lledó et al, 2019). It has been suggested that sediment shear strength can influence macrofaunal diversity patterns (Chuar et al, 2020); however, it is currently unknown if subtle changes in nodule geochemistry influence biodiversity and community composition.…”
Section: Discussionmentioning
confidence: 99%
“…As the presence of polymetallic nodules reduces the substrate availability for metazoan meiobenthos not dependent on polymetallic nodules, nodule-free areas in the GSR exploration license area have a higher nematode density than nodule-rich areas (Pape et al, 2021). Deep-sea metazoan meiobenthos occurs predominantly in the upper 5 cm of sediment, whereupon >60% live in the surface 1 cm and <10 % in the 4–5cm layer (Vincx et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…We used different nodule sizes, to investigate if nodule size and height affect recovery. None of the artificial nodules used in this study mimics the high porosity of natural nodules (Hein et al, 2020 ), and would not be able to aid restoration of nodule crevice fauna (Pape et al, 2021 ; Thiel et al, 1993 ).…”
Section: Discussionmentioning
confidence: 99%
“…Removal of nodules may be especially critical for the distinct microbial, foraminiferal, and faunal communities living on and in the nodules. The habitat for communities living in the crevices of porous polymetallic nodules (Pape et al, 2021 ; Thiel et al, 1993 ) will be lost. The faunal composition in the crevices differs from that in the sediment surrounding the nodules (Thiel et al, 1993 ), but crevice fauna is to our current knowledge not endemic to the nodule crevices and only adds little to the total meiobenthic abundance and diversity (Pape et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation